2016
DOI: 10.1007/s10867-016-9426-3
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic nanosized iron oxides obtained from cultivation of iron bacteria from the genus Leptothrix

Abstract: A detailed investigation of nanostructured iron oxides/(oxy)hydroxides gathered after cultivation of bacteria from the genus Leptothrix as iron (II) oxidizers is presented. A specific type of medium is selected for the cultivation of the bacteria. Results for sediment powder and bio-film on glass substrate samples from the same media are discussed. XRD, Raman spectroscopy, SEM, and TEM images and PPMS measurements are used to prove the exact composition of the biogenic products and to interpret the oxidation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…These three genera accounted for ∼24% of the total genera, indicating that they can survive in such tailing environments well. They have been widely reported to produce twisted stalks or straight tubular sheath-like biogenic Fe minerals. , For example, Leptothrix genera were found to promote Fe­(II) oxidation and biogenic Fe minerals formation . Hashimoto et al reported the straight tube-shaped biogenic Fe minerals formed by the Leptothrix genera.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These three genera accounted for ∼24% of the total genera, indicating that they can survive in such tailing environments well. They have been widely reported to produce twisted stalks or straight tubular sheath-like biogenic Fe minerals. , For example, Leptothrix genera were found to promote Fe­(II) oxidation and biogenic Fe minerals formation . Hashimoto et al reported the straight tube-shaped biogenic Fe minerals formed by the Leptothrix genera.…”
Section: Discussionmentioning
confidence: 99%
“…16,22 For example, Leptothrix genera were found to promote Fe(II) oxidation and biogenic Fe minerals formation. 50 Hashimoto et al 51 reported the straight tube-shaped biogenic Fe minerals formed by the Leptothrix genera. Thiobacillus-type bacteria are capable of Fe oxidization and precipitation, 52 and produce rod-like and sheathed ferric arsenate.…”
Section: Formation Of Biogenic Fe Minerals In Suboxicmentioning
confidence: 99%
“…Moreover, culture-based BIOX (referred to as cBIOX hereafter) sheaths have been investigated using bacterial strains of Leptothrix spp. from the perspective of material science. Our previous study has demonstrated that the chemical compositions and crystallinity of cBIOX products can be modified by an alteration of Si concentrations in the culture medium . The findings intriguingly suggested that there is plenty of scope for desired improvements in the cBIOXs as highly functional materials according to the industrial demand.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial culture systems using isolated strains of a sheath-forming iron oxidizing bacterium L. cholodnii have recently been established to prepare tubular iron oxide sheaths under laboratory conditions, properties of which were quite similar to those of nBIOXs. In addition, experimental improvements showed that chemical compositions and crystallinity of the culture-based BIOXs (hereafter referred to as “cBIOXs”) could be controlled optionally by modifying the compositions of culture media, demonstrating clearly that the refined method with cBIOXs could compensate for the shortcomings of nBIOX. More recently, the method has been revised to create unprecedented cBIOX sheaths containing various metallic elements toward an improvement and innovation of the functionality .…”
Section: Introductionmentioning
confidence: 99%